Asparaginase-associated pancreatitis in childhood acute lymphoblastic leukaemia: an observational Ponte di Legno Toxicity Working Group study. Issue 9 (September 2017) - Wolthers, Benjamin O; Frandsen, Thomas L; Baruchel, André; Attarbaschi, Andishe; Barzilai, Shlomit; Colombini, Antonella; Escherich, Gabriele; Grell, Kathrine; Inaba, Hiroto; Kovacs, Gábor; Liang, Der-Cherng; Mateos, Marion; et al.
Summary: Background: Survival for childhood acute lymphoblastic leukaemia surpasses 90% with contemporary therapy; however, patients remain burdened by the severe toxic effects of treatment, including asparaginase-associated pancreatitis. To investigate the risk of complications and risk of re-exposing patients with asparaginase-associated pancreatitis to asparaginase, 18 acute lymphoblastic leukaemia trial groups merged data for this observational study. Methods: Patient files from 26 trials run by 18 trial groups were reviewed on children (aged 1·0–17·9 years) diagnosed with t(9;22)-negative acute lymphoblastic leukaemia between June 1, 1996, and Jan 1, 2016, who within 50 days of asparaginase exposure developed asparaginase-associated pancreatitis. Asparaginase-associated pancreatitis was defined by at least two criteria: abdominal pain, pancreatic enzymes at least three times the upper limit of normal (ULN), and imaging compatible with pancreatitis. Patients without sufficient data for diagnostic criteria were excluded. Primary outcomes were defined as acute and persisting complications of asparaginase-associated pancreatitis and risk of re-exposing patients who suffered an episode of asparaginase-associated pancreatitis to asparaginase. Data were collected from Feb 2, 2015, to June 30, 2016, and analysed and stored in a common database at Rigshospitalet, Copenhagen, Denmark. Findings: Of 465 patients with asparaginase-associated pancreatitis, 33 (8%) of 424 with available data needed mechanical ventilation, 109 (26%) of 422 developed pseudocysts, acute insulin therapy was needed in 81 (21%) of 393, and seven (2%) of 458 patients died. Risk of assisted mechanical ventilation, need for insulin, pseudocysts, or death was associated with older age (median age for patients with complications 10·5 years [IQR 6·4–13·8] vs without complications 6·1 years [IQR 3·6–12·2], p<0·0001), and having one or more affected vital signs (fever, hypotension, tachycardia, or tachypnoea; 96 [44%] of 217 patients with affected vital signs vs 11 [24%] of 46 patients without affected vital signs, p=0·02). 1 year after diagnosis of asparaginase-associated pancreatitis, 31 (11%) of 275 patients still needed insulin or had recurrent abdominal pain or both. Both the risk of persisting need for insulin therapy and recurrent abdominal pain were associated with having had pseudocysts (odds ratio [OR] 9·48 [95% CI 3·01–35·49], p=0·0002 for insulin therapy; OR 11·79 [4·30–37·98], p<0·0001 for recurrent abdominal pain). Within 8 years of asparaginase-associated pancreatitis, risk of abdominal symptoms dropped from 8% (26 of 312) to 0% (0 of 35) but the need for insulin therapy remained constant (9%, three of 35). 96 patients were re-exposed to asparaginase, including 59 after a severe asparaginase-associated pancreatitis (abdominal pain or pancreatic enzymes at least three times the ULN or both lasting longer than 72 h). 44 (46%) patients developed a second asparaginase-associated pancreatitis, 22 (52%) of 43 being severe. Risk of persisting need for insulin or abdominal pain after having had two versus one asparaginase-associated pancreatitis did not differ (three [7%] of 42 vs 28 [12%] of 233, p=0·51). Risk of a second asparaginase-associated pancreatitis was not associated with any baseline patient characteristics. Interpretation: Since the risk of a second asparaginase-associated pancreatitis was not associated with severity of the first asparaginase-associated pancreatitis and a second asparaginase-associated pancreatitis did not involve an increased risk of complications, asparaginase re-exposure should be determined mainly by the anticipated need for asparaginase for antileukaemic efficacy. A study of the genetic risk factors identifying patients in whom asparaginase exposure should be restricted is needed. Funding: The Danish Childhood Cancer Foundation and The Danish Cancer Society (R150-A10181).